Improved high‐temperature electrical properties of polypropylene insulation material by grafting styrene - Xinhua Dong; Qing Shao; Yuanbo Cai; Qi Zhang; Wenjia Zhang; Shixun Hu; Shangshi Huang; Wei Wang; Qi Li; Jinliang He (High Voltage, 2025)
Abstract The electrical properties of polypropylene (PP) insulation material decrease dramatically at high temperature, which limits its application in harsh environments. This study investigates how grafting styrene (St) improves the high‐temperature electrical properties of PP. Compared with pure PP, the space charge of the St‐grafted PP (PP‐g‐St) samples is suppressed, the volume resistivity is significantly improved, and the breakdown strength at room temperature (30°C) and high temperature (90 and 110°C) is increased by 35.04%, 36.98% and 34.86%, respectively. The results show that the side chains generated by grafted St can increase the number of spherulites and improve the crystallinity, making the boundaries of the spherulites tortuous and narrow, which is not conducive to the formation of low‐density regions. At the same time, because of the entanglement of grafted side chains and the presence of deep traps inside the PP‐g‐St samples, which inhibit the injection and migration of carriers, the effect of high temperature on the free volume is weakened. Consequently, the ability to capture charges at high temperature is enhanced, leading to an improvement in the high‐temperature electrical properties of PP. This research can provide a reference for the development of high‐performance grafted PP insulation materials.